Bronchial reactivity to inhaled hypertonic saline solutions in children with cystic fibrosis - S.I. Ilchenko; A.O. Fialkovska; K.V. Skriabinа; S.G. Ivanus (Zaslavsky O.Yu., 2022)
Background. Inhaled hypertonic saline solutions (IHSS) are included in the list of mandatory prescriptions in the treatment of cystic fibrosis (CF). However, some patients with CF may develop bronchial hyperreactivity (BHR), which may be the cause of violation of the treatment protocol. The purpose is to study the state of bronchial reactivity to IHSS and its dependence on the clinical, functional and microbiological features of CF course in children. Materials and methods. Forty children with CF were examined. All of them underwent general clinical, molecular genetic, laboratory and microbiological examination. Instrumental methods included spirometry, measurement of fractional exhaled nitric oxide, X-ray and computer tomography of the chest. To determine the individual tolerance of inhalations of hypertonic sodium chloride solution (HSCS), the research protocol proposed by E.P. Dellon et al. was used. Results. According to the results of the research protocol, 17 (42.5 %) patients with CF had BHR to HSCS. The highest frequency of BHR was found in children with a severe CF course. There was no dependence of BHR in CF patients on allergic pathology and a burdened allergic history. Assessment of the tolerance of HSCS before prescribing basic therapy is important. Early functional signs of BHR, which may require the preventive administration of short-acting β2-agonists when using HSCS in children with CF, are as follows: reduction in forced expiratory volume in 1 second by 7 % and maximal expiratory flow at 25 % by 6 % when using 3% HSCS. Conclusions. The presence of BHR in patients with CF may interfere with adequate basic therapy by inhalation. The prescription of IHSS to patients with CF should be personalized with the determination of individual sensitivity of a person to predict a positive therapeutic effect.